Preparation and Evaluation Of Lip Balm Containing Apricot Seed Oil As Moisturizer - Fajar, In Rahmi Fatria; Fitri, Dewi Rahma; Napitupulu, Fitra (Politeknik Kesehatan Kemenkes Jakarta II, 2024)
Lip balm is a preparation used or applied on the lips to protect the lips from adverse environmental effects and prevent dry lips. Apricot seed oil is one of the oils that contain essential fatty acids, namely linoleic acid and oleic acid, thus it can be used as an excellent skin moisturizer. Objective this study aims to make a lip balm preparation formula containing apricot seed oil as a lip moisturizer. The research method used was an experimental design which included testing the quality of the oil, making lip balm preparations with optimization of apricot oil concentration, evaluated the quality, safety, and efficacy. The results active ingredients of apricot oil contained linoleic acid, oleic acid, palmitic acid, α-linolenic acid, and stearic acid. All preparations met the quality requirements as a homogeneous lip balm preparation with a melting point of 58oC - 60oC, pH 5.80 - 6.06. Safe to use and non-irritating. Optimization concentrations of 2.5%, 5%, 7.5%, and 10% have the effectiveness of moisturizing lips with an average percentage of increase in lip moisture after 4 weeks of use, namely 18.6%, 28.8%, 45.4%, and 65.6%. Conclusion apricot seed oil can be formulated as lip balm preparations that met quality requirements and have been tested to be safe for use. Lip balm preparations containing 10% apricot seed oil have been able to increase moisture on the lips.